Rent Dispersion in the US Agricultural Insurance Industry - Smith, Vincent H.; Glauber, Joseph W.; Dismukes, Robert (International Food Policy Research Institute, 2016)
A central, but inadequately explored issue with respect to subsidized crop insurance programs concerns the costs of delivering insurance coverage to farmers. This study examines that issue in the context of the heavily subsidized US crop insurance program which has often been put forward as a model for agricultural insurance programs in other countries. US Government programs often rely on private firms to deliver income transfers or services, which then establish their own rent-seeking lobbies, which are shared with input suppliers. This rent dispersion process is examined in the context of the U.S. agricultural insurance industry, which receives as much as one third of the annual subsidies that support the federal crop insurance program. We find that as total payments to insurance companies increased between 2001 and 2009, an increasingly large share of the agricultural insurance industry’s rents accrued to insurance agents, although in markets where insurance companies possessed some oligopsony power, agent payments are smaller. The findings also suggest that the insurance industry (companies and independent agents) would almost surely provide the same service for substantially less than the gross revenues from the subsidies and underwriting gains they received.